An experimental study of pH distributions within an electricity-producing biofilm by using pH microelectrode. (10th October 2017) - Hou, Junxian; Liu, Zhongliang; Zhou, Yu; Chen, Wenwen; Li, Yanxia; Sang, Lixia
Graphical abstract: Highlights: This study quantified the spatial pH distributions within the Geobacter biofilm. The detected pH level was as low as 5.57 in a 350 μm thick Geobacter biofilm. The average pH levels within Geobacter biofilm decreased over time. Abstract: This study quantified the spatial pH distributions within an electricity-producing biofilm and its concentration boundary layer, as well as the bulk solution by employing pH microelectrode. The relationship between pH distributions and current densities was explored. It was found that (1) pH level near the anode surface was detected as low as 5.57 compared to 6.90 of the bulk solution across a 350 μm thick Geobacter biofilm; (2) the average pH levels within the biofilm decreased over time; (3) pH variations within the biofilm shifted the midpoint potential of Cyclic Voltammetry with 59.0 mV per pH; (4) pH level near the anode surface was as low as 4.91 for a 25 mM phosphate buffer solution compared to 5.73 of that for the 100 mM. Furthermore, a method was recommended to estimate the thickness of biofilm by plotting the derivative of pH-depth profile.